Network pharmacology and anticancer mechanism study of Dendrobium nobile dendrobine in the treatment of colorectal cancer - Pei Luo; Can Huang; Jun Guo; Xin Yao; Chao Pan; Aijin Bao; Fei Li; Ying-ying Li (Discover Oncology)
Abstract Objective This study aims to explore the potential targets and anticancer mechanisms of dendrobine from Dendrobium nobile in the treatment of colorectal cancer through network pharmacology, and to experimentally validate its specific effects. Methods Initially, potential targets of dendrobine were identified using the ITCM Traditional Chinese Medicine database, while colorectal cancer-related genes were obtained from the NCBI Gene database, with the intersection of these datasets taken for further analysis. Functional enrichment analysis was conducted using the Metascape database, and a protein–protein interaction (PPI) network was constructed. Additionally, cell culture, cell proliferation assays, and wound healing assays were performed. The Wnt/β-catenin and NF-κB/COX-2/PGE2 signaling pathways were analyzed using PCR and Western blot experiments. Results The PPI network constructed from 152 intersecting genes revealed that these genes play crucial roles in processes such as cell proliferation, apoptosis, and signal transduction. Cell-based assays demonstrated that dendrobine significantly inhibits the proliferation and migration of colorectal cancer cells. Furthermore, PCR and Western blot results indicated that dendrobine suppresses colorectal cancer cell proliferation and migration by modulating the Wnt/β-catenin and NF-κB/COX-2/PGE2 signaling pathways. Conclusion Dendrobine exhibits significant anticancer potential against colorectal cancer by regulating the Wnt/β-catenin and NF-κB/COX-2/PGE2 signaling pathways, providing a theoretical foundation and experimental evidence for its therapeutic application in colorectal cancer.